The Quantitative Analysis of Transparency and Accountability of Village Fund Management in Klaten Regency - Minarni, Sarida; Raharjo, Paiman; Soemarono, Triyuni; Effendy, Khasan; Rachmatsyah, T.Herry (Journal of Posthumanism, 2025)
This study aims to determine the effect of budget target clarity, reporting systems, organizational commitment and society participation in village fund management accountability in Klaten Regency. The sample of this study with 256 respondents. The method of determining the sample using the saturated sample method and data collection using a questionnaire. Data were analyzed using SEM PLS. Based on the results of this study indicate that the budget target clarity, reporting systems, organizational commitment and society participation had a positive effect on the accountability of village fund management in Klaten Regency. This showed that better the budget target clarity, reporting systems, organizational commitment and society participation, the accountability of village fund management in Klaten Regency would be better.